2019
DOI: 10.1007/s00401-018-1951-7
|View full text |Cite
|
Sign up to set email alerts
|

Pathological, imaging and genetic characteristics support the existence of distinct TDP-43 types in non-FTLD brains

Abstract: TDP-43 is present in a high proportion of aged brains that do not meet criteria for frontotemporal lobar degeneration (FTLD). We determined whether there are distinct TDP-43 types in non-FTLD brains. From a cohort of 553 brains (Braak neurofibrillary tangle (NFT) stage 0-VI), excluding cases meeting criteria for FTLD, we identified those that had screened positive for TDP-43. We reviewed 14 different brain regions in these TDP-43 positive cases and classified them into those with "typical" TDP-43 immunoreactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(121 citation statements)
references
References 54 publications
10
111
0
Order By: Relevance
“…Recent study also suggested distinct TDP-43 types present in non-FTD brains, typical TDP-43 αtype and newly characterized β-type 65 . TDP-43 α-type is the typical form conventionally observed in temporal, frontal and brainstem regions.…”
Section: Discussionmentioning
confidence: 87%
“…Recent study also suggested distinct TDP-43 types present in non-FTD brains, typical TDP-43 αtype and newly characterized β-type 65 . TDP-43 α-type is the typical form conventionally observed in temporal, frontal and brainstem regions.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, in most cases, the lesion type was perivascular [29]. TDP-43 associated with NFT known as TDP-43 type β [37] was the least common type of lesion observed. There was no significant difference in the final clinical diagnoses rendered before death or in the Mini-Mental State Examination [38] or Clinical Dementia Rating Scale sum of boxes [39] scores at the last examination before death.…”
Section: Resultsmentioning
confidence: 95%
“…This may suggest that symptomatic PART may be linked to TDP-43 extending beyond limbic regions. Given our recent report of two types of TDP-43, type α and type β, and that type α is characterized by higher TDP-43 stages [37], it is possible that TDP-43 in symptomatic PART is different from TDP-43 in asymptomatic definite PART.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of TDP-43 phenotypes in FTLD is well studied. 4,5,17 Abnormal TDP-43 structures are typically classified into neuronal cytoplasmic inclusions, neuronal preinclusions, neuronal intranuclear inclusions, and dystrophic neurites and the distribution of and presence of these TDP-43 features has been used to subtype FTLD and AD cases. [18][19][20] Consistent brain regions are affected by FTLD and AD and can be more readily assessed for TDP-43 pathology.…”
Section: Discussionmentioning
confidence: 99%